RESEARCH ON THE PRINTING AND TECHNICAL PROPERTIES OF KRAFT PAPER INCORPORATING "COTTON CELLULOSE-INDUSTRIAL WASTE-PACULATE" - ESHBAEVA, ULBOSIN (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
In this study, to conserve valuable cotton cellulose, the paper pulp was composed of light industrial cocooning waste from our Republic (specifically, the mat and fiber produced during cocooning at the Margulon "IPAKCHI" joint-stock company) and secondary paper waste (MS-3A). Binders and adhesives were used in the preparation process. The kraft paper samples were prepared in the test laboratory of the "Global Komsco Daewoo" joint venture.